Perencanaan Sistem Penyaliran Tambang Batubara Sump RL 16 HW Barat Pit Tutupan, PT Pamapersada Nusantara, Kalimantan Selatan - Simamora, Eprilia; Ardian, Aldin; Nurcholis, Mohammad; Luwik Djanas Usup, Hepryandi (Jurnal Manajemen Teknologi & Teknik Sipil, 2024)
The coal mining activities conducted by PT Pamapersada Nusantara in the Pit Tutupan, South Kalimantan, employ an open pit mining system. This method creates exposed working surfaces that can accumulate rainwater runoff. This study aims to design a drainage system to manage water control in the western high wall area of RL 16, considering the impact of mining progression. The planning involves calculations for scheduled rainfall, rainfall intensity, estimated water discharge, open channel dimensions, culvert, and the number of pumps required to manage water in the pit sump. Using the Log Pearson III distribution, planned rainfall is determined at 101.499 mm for a 2-year return period and 134.782 mm for a 5-year return period. The rain catchment area at the research site in Sump RL 16 HW Barat is 84.83 hectares. The proposed trapezoidal channel design accommodates varying water discharges: 4.47 m³/s, 5.04 m³/s, 8.75 m³/s, 7.87 m³/s, 7.20 m³/s, and 3.77 m³/s for tertiary, secondary, and primary channels. The sump is designed to store two days’ worth of rainfall, with a capacity of 186,516 m³. Excess water is pumped to an external drainage system and settling pond using a Direct Multistage Pump system. The primary pump planned is the Multiflo 420 EX, complemented by a Warman 8/6 AH booster pump. Both pumps utilize TYCO PE100 HDPE pipes, ensuring efficient water transfer to the drainage system and settling pond, optimizing mine water management. The research results can be a reference for planning mine drainage systems with similar characteristics.